2022
DOI: 10.1002/ajoc.202200399
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric 3‐Allenylation of Indoles via Remote Stereocontrolled 1,10‐Additions of Alkynyl Indole Imine Methides

Abstract: A chiral phosphoric acids catalyzed regio‐ and enantioselective 1,10‐conjugate addition of 2‐arylindoles to alkynyl indole imine methides formed in situ from α‐(6‐indolyl)propargylic alcohols has been developed. With the established system, organocatalytic asymmetric 3‐allenylation of indoles was realized, affording a broad scope of axially chiral tetrasubstituted allenes bearing two indole motifs in high yields with stereoselectivities. Importantly, the organocatalytic remote stereocontrolled strategy disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Notably, several types of auxiliary groups have been developed, enabling the corresponding alcohols to be successfully involved in organocatalytic enantioselective reactions. As shown in Scheme B,C, these functionalized alcohols dehydrated under acidic conditions to in situ generate o -quinone methides ( o -QMs), aza- o -quinone methides (aza- o -QMs), p -quinone methides ( p -QMs), aza- p -quinone methides (aza- p -QMs), 7-methyleneindoles, 3-methyleneindoles, 2-methyleneindoles, and 6-methyleneindoles, , followed by conjugate addition to complete the formal enantioselective nucleophilic substitution reactions. Particularly, a breakthrough in the field of organocatalytic construction of chiral tetraarylmethanes from tertiary alcohols was made by Sun and co-workers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several types of auxiliary groups have been developed, enabling the corresponding alcohols to be successfully involved in organocatalytic enantioselective reactions. As shown in Scheme B,C, these functionalized alcohols dehydrated under acidic conditions to in situ generate o -quinone methides ( o -QMs), aza- o -quinone methides (aza- o -QMs), p -quinone methides ( p -QMs), aza- p -quinone methides (aza- p -QMs), 7-methyleneindoles, 3-methyleneindoles, 2-methyleneindoles, and 6-methyleneindoles, , followed by conjugate addition to complete the formal enantioselective nucleophilic substitution reactions. Particularly, a breakthrough in the field of organocatalytic construction of chiral tetraarylmethanes from tertiary alcohols was made by Sun and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, suitable reaction partners and catalytic systems are also key elements to successful stereocontrol. Fully aware of the difficulties but also of the potential benefits, as part of our ongoing interest in the field of organocatalytic asymmetric reactions of the functionalized alcohols, ,,, we decided to develop an organocatalytic enantioselective synthesis of chiral tetraarylmethanes from racemic triarylmethanols (Scheme E).…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation, we employed 2‐arylindoles 51 as nucleophiles to react with α‐(6‐indolyl) propargylic alcohols 48 in the presence of chiral phosphoric acid C21 and obtained 1,10‐adducts 52 containing axially chiral tetrasubstituted allenes and indole motifs in 72–91% yield with 80–92% ee (Scheme 14). [27] Notably, proof again that the organocatalytic enantioselective 1,10‐conjugate addition of in situ formed propargylic 6‐methylene‐6 H ‐indoles from α‐(6‐indolyl) propargylic alcohols provided an efficient tool for the asymmetric construction of axially chiral tetrasubstituted allenes.…”
Section: Asymmetric 110‐conjugate Additionmentioning
confidence: 94%
“…10 In particular, the CPA-catalyzed reactions of functionalized propargylic alcohols provided robust access to axially chiral allenes via asymmetric conjugate addition of in situ formed propargylic p -quinone methides ( p -QMs), 11 propargylic aza- p -quinone methides (aza- p -QMs), 12 and propargylic methyleneindoles. 13 Independently, Shi and coworkers realized the asymmetric synthesis of aryl-pyrroloindoles with axial and central chirality via an organocatalytic asymmetric (2 + 3) cyclization of 3-arylindoles with propargylic alcohols (Scheme 1A). 14 They also found that the auxiliary group of propargylic alcohols played a key role in controlling the enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%